Oxford international lower secondary english Book 3 For grade 8 - Sullivan, Eve; Mertin, Patricia; Saunders, Mark (Karachi: Oxford university press, 2023)
This edition of Oxford International Lower Secondary English gives students the skills they need to become confident communicators with a strong grasp of English language, vocabulary and grammar. Students discover the joy of learning through speaking and listening, reading extracts from around the world, writing and performing.
Keywords: English